Ventilation rates in naturally ventilated primary schools in the UK; Contextual, Occupant and Building-related (COB) factors. (15th August 2020) - Korsavi, Sepideh Sadat; Montazami, Azadeh; Mumovic, Dejan
Abstract: Indoor Air Quality (IAQ) in classrooms is assessed by CO2 levels and Ventilation Rates (VRs). Factors affecting VRs fall into C ontextual, O ccupant and B uilding (COB) related factors. This study investigates how VRs are affected by COB factors in 29 naturally-ventilated classrooms in the UK during Non-Heating and Heating seasons. B uilding-related factors classify classrooms with high or low potentials for natural ventilation, with 45% of classrooms having high potentials. C ontextual factors including season, operative temperature (Top ), outdoor temperature (Tout ), 'Top -Tout ' and air density can limit or increase VRs. O ccupant-related factors classify occupant's good or poor practice of environmental adaptive behaviours. 'Open area' as a reflection of all COB factors is strongly correlated with ventilation rates. Results show that 12% and 19% of variations in ventilation rates are explained by open areas during non-heating and heating seasons, respectively. Findings highlight that to have VR of 8 ± 1.28 l/s.p during non-heating seasons and VR of 8 ± 1.07 l/s.p during heating seasons, average open areas of 3.8 m 2 and 2 m 2 are required, respectively. This difference can mostly be explained by temperature difference between inside and outside. Results show COB factors need to be considered holistically to maintain adequate VRs. Classrooms in which all COB factors are met provide average VR of 11 l/s.p and classrooms in which none of COB factors are met provide average VR is 3.1 l/s.p. This study highlights that 40% of classrooms according to EN 13779 and 80% of classrooms according to ASHRAE Standard fail to provide adequate VRs. Highlights: Same openings provide different airflow rates due to temperature difference. Seasonal changes should be considered in openings' design to provide air quality. When contextual, building and occupant factors are met, ventilation is 11 l/s.p. 40% of classrooms according to EN 13779 fail to provide adequate ventilation rate. 80% of classrooms according to ASHRAE fail to provide adequate Ventilation rates.